2017
DOI: 10.1139/cjss-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Dissipation of Seven Herbicides in a Biobed Matrix

Abstract: Cold winters and short, warm summers in the Canadian prairies pose a challenge for the effectiveness of onfarm biobeds for degrading agricultural pesticides. A thermo-gradient plate was used to evaluate the effect of temperature on the dissipation kinetics of seven commonly used herbicides applied to a biobed matrix composed of materials typically available on a farm. The dissipation of all seven herbicides increased with increasing incubation temperature and duration. 2,4-D, bromoxynil, and thifensulfuron-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…The polynomial model indicated a lower accumulation of dry matter with 54 mm of rainfall, similarly to the untreated control ( Figure 2C). It is important to note that the irrigation conditions after the soybean planting presumably favored a maximum herbicide dissipation, since 2,4-D is easily degraded via hydrolysis and oxidation in wet conditions (Cessna et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polynomial model indicated a lower accumulation of dry matter with 54 mm of rainfall, similarly to the untreated control ( Figure 2C). It is important to note that the irrigation conditions after the soybean planting presumably favored a maximum herbicide dissipation, since 2,4-D is easily degraded via hydrolysis and oxidation in wet conditions (Cessna et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The soil residue of dicamba has more severe detrimental effects on soybean than 2,4-D, what may be related to the slow dissipation of dicamba in the environment (Kah et al 2007), whereas the 2,4-D dissipation occurs easily via hydrolysis and oxidation in wet conditions (Cessna et al 2017). Similar observations have been made for soybean, cotton and sesame (Prostko et al 2003, Thompson et al 2007, Sperry et al 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, increasing soil temperature is also associated with the increased biological activity of the soil and degradation. Cessna et al [31] showed that degradation of metsulfuron-methyl and thiencarbazonemethyl in cold seasons was lower than in warm seasons with higher temperatures.…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…Weed control with fall applications can be more consistent than with spring applications, which are dependent on precipitation after application. Fall applications of these herbicides on the northern Great Plains made after soil temperatures, and subsequently microbial activity, have decreased, do not result in significant degradation of active ingredient in the soil prior to weed emergence the following spring (Cessna et al 2017, Anonymous 2020).…”
Section: Introductionmentioning
confidence: 99%